2019
DOI: 10.1073/pnas.1820719116
|View full text |Cite
|
Sign up to set email alerts
|

Redox control on nitrogen isotope fractionation during planetary core formation

Abstract: The present-day nitrogen isotopic compositions of Earth’s surficial (15N-enriched) and deep reservoirs (15N-depleted) differ significantly. This distribution can neither be explained by modern mantle degassing nor recycling via subduction zones. As the effect of planetary differentiation on the behavior of N isotopes is poorly understood, we experimentally determined N-isotopic fractionations during metal–silicate partitioning (analogous to planetary core formation) over a large range of oxygen fugacities (ΔIW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 87 publications
(213 reference statements)
5
46
2
Order By: Relevance
“…Aligning with the conventional views backed by several studies [51][52][53] , in this study we assume limited N isotope fractionation during alloy-silicate differentiation 48 such that N isotopic composition of the iron meteorites can be directly traced to the N isotopic composition of the bulk material that made up their parent bodies. If there was significant fractionation of N isotopes during alloy-silicate equilibration 49 , then the material accreted by the parent bodies of iron meteorites should have had higher 15 N/ 14 N ratios relative to those measured in the iron meteorites themselves. However, as long as the alloy-silicate differentiation for all magmatic iron meteorites occurred at largely similar fO2 conditions 26,54 , the only estimate that would be impacted are the contribution of CC and NC material to the N budget in the BSE.…”
Section: Effects Of Planetary and Cosmic Processes On The Alteration Of 15 N/ 14 N Ratios Of Iron Meteoritesmentioning
confidence: 99%
“…Aligning with the conventional views backed by several studies [51][52][53] , in this study we assume limited N isotope fractionation during alloy-silicate differentiation 48 such that N isotopic composition of the iron meteorites can be directly traced to the N isotopic composition of the bulk material that made up their parent bodies. If there was significant fractionation of N isotopes during alloy-silicate equilibration 49 , then the material accreted by the parent bodies of iron meteorites should have had higher 15 N/ 14 N ratios relative to those measured in the iron meteorites themselves. However, as long as the alloy-silicate differentiation for all magmatic iron meteorites occurred at largely similar fO2 conditions 26,54 , the only estimate that would be impacted are the contribution of CC and NC material to the N budget in the BSE.…”
Section: Effects Of Planetary and Cosmic Processes On The Alteration Of 15 N/ 14 N Ratios Of Iron Meteoritesmentioning
confidence: 99%
“…Hashizume and Sugiura 1995) and carbonaceous chondrites (δ 15 N CI/CM = -6 to +56‰, excluding Bells (CM2); Kerridge 1985; Alexander et al 2012) largely overlap. 8 Since only enstatite chondrites have negative δ 15 N values, Javoy et al (1986) suggested that they are the source of nitrogen in Earth's primitive mantle (δ 15 N ≈ -40‰; Palot et al 2012;Cartigny and Marty 2013;Dalou et al 2019). As outlined in Sect.…”
Section: Constraints From Nitrogen Isotopesmentioning
confidence: 99%
“…It is noteworthy that the nitrogen isotopic signature of the modern (upper) terrestrial mantle (δ 15 N ≈ -5 ± 2‰ in diamonds and mid-ocean ridge basalts; Cartigny and Marty 2013) has previously been interpreted to reflect that CI/CM-like planetesimals were the major sources of nitrogen on Earth (e.g., ). Yet, Li et al (2016) and Dalou et al (2019) recently showed that core formation, possibly coupled with degassing, could have increased the δ 15 N mantle value from an enstatite chondrite-like signature to the present-day value. The degree of N isotope fractionation, however, depends on the redox conditions and on N speciation.…”
Section: Constraints From Nitrogen Isotopesmentioning
confidence: 99%
“…During the main epoch of accretion, rocky planets likely melt entirely due to release of potential energy [28], of short-lived radioactive isotopes as in the Solar System [54,82], and thermal blanketing of the captured nebular proto-atmosphere [63,109]. As a result Fe metal, which is immiscible with silicate, is able to sink to the planet's centre forming a metal core (carrying with it elements with an affinity to chemically bind to Fe, such as Ni and limited amounts of light elements, e.g., H, C, N, O, S, Si, [17,31,55,57]). The silicate mantle left behind undergoes further differentiation, producing a crust and atmosphere.…”
Section: Terrestrial Planetsmentioning
confidence: 99%